2020
DOI: 10.3389/fimmu.2020.01866
|View full text |Cite
|
Sign up to set email alerts
|

Serine Supports IL-1β Production in Macrophages Through mTOR Signaling

Abstract: Intracellular metabolic programs tightly regulate the functions of macrophages, and previous studies have shown that serine mainly shapes the macrophage function via one-carbon metabolism. However, it is unknown whether serine modulates the macrophage function independent of one-carbon metabolism. Here, we find that serine deprivation lowers interleukin (IL)-1β production and inflammasome activation, as well as reprograms the transcriptomic and metabolic profile in M1 macrophages. Intriguingly, supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 71 publications
3
32
0
1
Order By: Relevance
“…The role of serine on cancer cell and T-cell proliferation is well recognized to provide substrates for the synthesis of nucleotides, NADPH, and glutathione ( 41 , 42 ). It was recently shown that serine supports lipopolysaccharide-induced IL-1β production in macrophages ( 43 ). However, how serine engages in host-pathogen interaction, and whether it contributes to host survival, was largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The role of serine on cancer cell and T-cell proliferation is well recognized to provide substrates for the synthesis of nucleotides, NADPH, and glutathione ( 41 , 42 ). It was recently shown that serine supports lipopolysaccharide-induced IL-1β production in macrophages ( 43 ). However, how serine engages in host-pathogen interaction, and whether it contributes to host survival, was largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal macrophages were isolated as in our previous study ( 10 ). Mice were injected intraperitoneally with 2 ml of 4% sterile thioglycolate, and peritoneal macrophages were collected via peritoneal lavage with 5 ml cold phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…Essential amino acids, which cannot be sufficiently synthesized by the body and must obtained from dietary sources, are crucial for the function of immune cells ( 8 ). For instance, methionine is critical for T-cell activation ( 9 ), and serine or tryptophan metabolism is associated with macrophage biology ( 10 , 11 ). Non-essential amino acids can be synthesized endogenously, but they switch into being conditionally essential when the synthesis rates cannot meet the demand of the host ( 8 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to participating in protein synthesis, glycine is a precursor of peptides, nucleic acids as well as methyl donors. Upon LPS stimulation, the levels of intracellular glycine and glycine metabolites such as glutathione (GSH) and Sadenosylmethionine (SAM) increased (37)(38)(39). Interestingly, adding glycine to the serine-deprived medium failed to rescue IL-1b secretion in macrophages upon LPS stimulation (38).…”
Section: Glycine Metabolism In Macrophagesmentioning
confidence: 99%